Geotextile revetment filters - Lawson, C.R. (Geotextiles and geomembranes, 1992)
The use of geotextiles as revetment filters comprised one of the earliest applications for these materials. In performing its role within the revetment structure the geotextile must meet specific mechanical and hydraulic criteria. The mechanical criteria presented in the paper are based on empirical relationships derived by correlating analysed in-situ performance with appropriate laboratory mechanical test methods. The hydraulic criteria presented in the paper rationalizes the plethora of published geotextile filter criteria, and consider such variables as geometric and hydrodynamic stability, mode of water movement through the geotextile filter, and type of foundation soil to be protected.